Laser performance of in-band pumped Er : LiYF4 and Er : LiLuF4 crystals. (1st March 2016) - Gorbachenya, K N; Kurilchik, S V; Kisel, V E; Yasukevich, A S; Kuleshov, N V; Nizamutdinov, A S; Korableva, S L; Semashko, V V
Abstract: Spectroscopic properties of Er : LiLuF4 and Er : LiYF4 crystals in the spectral region near 1.5 μm and the lasing characteristics of these crystals under in-band pumping at a wavelength of 1522 nm are studied. With the Er : LiLuF4 crystal, the maximum slope efficiency with respect to the absorbed pump power was 44% at a wavelength of 1609 nm. Continuous-wave operation of an inband pumped Er : LiYF4 laser is obtained for the first time. The output power at a wavelength of 1606 nm was 58 mW with a slope efficiency of 21%.